The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s0104-56872009000400003
|View full text |Cite
|
Sign up to set email alerts
|

Processamento linguístico e processamento auditivo temporal em crianças com distúrbio específico de linguagem

Abstract: Background: several studies suggest the association of specific language impairment (SLI) to deficits in auditory processing.It has been evidenced that children with SLI present deficit in brief stimuli discrimination. Such deficit would lead to difficulties in developing phonological abilities necessary to map phonemes and to effectively and automatically code and decode words and sentences. However, the correlation between temporal processing (TP) and specific deficits in language disorders -such as syntacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 14 publications
1
18
0
13
Order By: Relevance
“…In the present review, two studies (4,32) evaluated MMN in children with this disorder. The literature has provided evidence that discrimination of auditory stimuli would be compromised in children with SLI (47) . Therefore, poor performance in auditory processing may affect abilities to discriminate speech sounds, which could consequently affect perception and speech production (48) , a fundamental aspect for the development of children's language.…”
Section: Discussionmentioning
confidence: 99%
“…In the present review, two studies (4,32) evaluated MMN in children with this disorder. The literature has provided evidence that discrimination of auditory stimuli would be compromised in children with SLI (47) . Therefore, poor performance in auditory processing may affect abilities to discriminate speech sounds, which could consequently affect perception and speech production (48) , a fundamental aspect for the development of children's language.…”
Section: Discussionmentioning
confidence: 99%
“…The associations between deficits in auditory tasks and language disorders are not clear and must be explained 25 .…”
Section: Temporal Aspects Of Auditionmentioning
confidence: 99%
“…A study developed with 18 subjects of similar age, of which eight had temporal lobe epilepsy and ten without cortical damage, it was observed that individuals with epilepsy had more deficits in auditory Figure 1 presents the publications [25][26][27][28][29][30][31][32][33][34][35] It was observed that, in most studies of individuals who had speech pathology, the temporal ordering ability was impaired, and FPT was the test most frequently used to assess this ability.…”
Section: Clinical Applications Of Frequency Patterns and Duration Patmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the studies that focus on language disorders in childhood have explained the biological and linguistic limits of clinical cases [1][2][3][4][5][6][7][8][9][10] , while other ones have approached the initial interactions 11,12 . On the other hand, studies in a enunciative perspective are recent, in particular those ones directed to the subjectivity in language.…”
Section: Introductionmentioning
confidence: 99%